Quantifying the return on investment of social and ecological data for conservation planning - Christopher R Field; Chris S Elphick (Environmental Research Letters, 2019)
The interdisciplinary nature of conservation problems is increasingly being incorporated into research, raising fundamental questions about the relative importance of the different types of knowledge and data. Although there has been extensive research on the development of methods and tools for conservation planning, especially spatial planning, comparatively little is known about the relative importance of ecological versus non-ecological data for prioritization, or the likely return on investment of incorporating better data. We demonstrate a simple approach for (1) quantifying the sensitivity of spatial planning results to different ecological and non-ecological data layers, and (2) estimating the potential gains in efficiency from incorporating additional data. Our case study involves spatial planning for coastal squeeze, a process by which development blocks coastal ecosystems from moving landward in response to sea-level rise. We show that incorporating spatial data on landowners’ likelihood of selling had little effect on identifying relative priorities but drastically changed the outlook for whether conservation goals could be achieved. Better data on the costs of conservation actions had the greatest potential to improve the efficiency of spatial planning, in some cases generating more than an order of magnitude greater cost savings compared to ecological data. Our framework could be applied to other systems to guide the development of spatial planning and to identify general rules of thumb for the importance of alternative data sources for conservation problems in different socio-ecological contexts.